Taxes and People in Israel - Wilkenfeld, Harold C. (Harvard Law School International Tax Program, 2014)
"In tax administration," writes the author, "all countries can learn from each other." This revealing case study of the development of Israel's tax system--a system which has dealt with the full panoply of problems that tax administrators must face and which is further characterized by heavy taxation--offers a wealth of noteworthy examples for other countries. Harold C. Wilkenfeld presents a detailed account of the historical and economic realities that forged Israel's elaborate tax structure from the Ottoman period to the present day. He scrutinizes such areas as the crises that Israel's tax administration faced shortly after the State achieved its independence, the problems which had to be solved, the formulation of administrative policy, the interplay of a developing civil service and a developing citizenry. All of these areas are viewed in the context of an evolving economy and a continuing external conflict. The author presents practical guidelines for countries interested in advancing the effectiveness of tax administration. For instance, many of the Israeli administration's tactics against tax evasion may be transplantable to other nations. Likewise, a number of the technical solutions to administrative problems of both direct and indirect taxes can certainly and readily be adapted to conditions in a number of developing countries. Taxes and People in Israel comes as a welcome addition to a field which offers few critical, historical studies of the entire tax system of a country. It will be of considerable interest to tax administrators and ought to be read by every new head of a tax administration. It should also prove a valuable source to public administrators, lawyers, sociologists, economists, and anyone concerned with giving fiscal advice to the developing countries.